Unspoken Rome : Absence in Latin Literature and Its Reception - Geue, Tom (Cambridge University Press, 2021)
Cover -- Half-title page -- Title page -- Copyright page -- Contents -- List of Figures -- Unspoken Rome: Acknowledgements -- List of Contributors -- Introduction -- Part I Absence in Text -- Chapter 1 Catullus' Sapphic Lacuna: A Palimpsest of Absences and Presences -- Chapter 2 Speaking Aposiopeseis: The (Generic) Sound of Silence in Statius' Thebaid' -- Chapter 3 Allegorical Absences: Virgil, Ovid, Prudentius and Claudian -- Chapter 4 Tamen apsentes prosunt pro praesentibus: Proxied Absences and Roman Comedy -- Chapter 5 Absence Left Wanting: The Groove in Ovid's Remedia -- Chapter 6 The Gaze on the Void: Hermeneutic Responses to Dido's First Appearance -- Part II Absence in Context -- Chapter 7 Speaking Silence in Cicero's Brutus and Tacitus' Dialogus de Oratoribus -- Chapter 8 Et sine auctore notissimi uersus: Unauthored Poetry and Rome's Authoritative Turn -- Chapter 9 Looking for the Emperor in Seneca's Letters -- Chapter 10 Marcus Aurelius: Medi()ations Not Medi(c)ations -- Chapter 11 Lost in Germania: The Absence of History in Tacitus' Ethnography -- Chapter 12 Conspicuous Absence: Tacitus' De Re Publica -- Part III Going Beyond -- Chapter 13 The Slave, Between Absence and Presence -- Chapter 14 In Search of the Lost City: The Enduring Absence of Pompeii -- Chapter 15 Omnibus umbra locis adero: Elena Ferrante and the Poetics of Absence -- Chapter 16 The Philology of Grief: Catullus 101 and Anne Carson's Nox -- Chapter 17 Absence, Metaphysically Speaking: From Reception to Instauration? -- Afterword Lights Out -- Bibliography -- General Index -- Index Locorum.